Micronucleus test in fish for in situ evaluation of the Sinos River water quality, in Brazil - Simões, Leonardo Airton Ressel; Dalzochio, Thaís; Goldoni, Angélica; Souza, Mateus Santos de; Rodrigues, Gabriela Zimmermann Prado; Petry, Ismael Evandro; Gehlen, Günther; Silva, Luciano Basso da (Ciência e Natura, 2019)
The Sinos River basin is impacted by industrial and agricultural activities, as well as by low rates of urban wastewater treatment. The purpose of this study was to monitor de Sinos River water quality using the micronucleus test in fish and the analysis of water physicochemical parameters. Bryconamericus iheringii specimens were captured in December 2013 (summer) and July 2014 (winter) at two sites located in the Sinos River: Caraá, in the upper section of the basin, and Parobé, in the middle section. After capture, animals were immediately killed and blood samples were collected for the micronucleus test. No significant differences were observed in micronucleus frequencies between sites and sampling periods. However, in the summer, nuclear abnormalities frequencies observed in Parobé were significantly higher than in Caraá. A higher frequency of nuclear abnormalities was also found in fish captured in Caraá during winter, in comparison with frequencies found in the summer. The results for the water physicochemical analysis showed values of total phosphorous, aluminum, lead, copper and iron above the allowed limits established by the Brazilian legislation. The nuclear abnormalities induction found in the present study may be associated to the presence of cytogenotoxic substances in the water.